Cobalt Used as a Novel and Reusable Catalyst: A New and One-Pot Synthesis of Isatin-Derived N,S-Acetals Using Substituted Isatins and Thiols - da Silva, Caren D. G.; Katla, Ramesh; dos Santos, Beatriz F.; Tavares Junior, José M. C.; Albuquerque, Tábata B.; Kupfer, Vicente L.; Rinaldi, Andrelson W.; Domingues, Nelson L. C. (Synthesis, 2019)
The synthesis of isatin-derived N,S-acetals using cobalt as a recyclable heterogeneous catalyst in batch and continuous flow is reported for the first time. The present protocol produced high yields, which can be observed from the reaction between ketimines and thiols. Such reactions can also be applied to a gram-scale. In addition, the catalyst is recyclable, economically-viable, and nontoxic as well as easy to prepare. The remarkable features of this new methodology are high conversion and cleaner reaction profiles.
Keywords: heterogeneous catalyst; isatin-derived N,S-acetals; cobalt(II) catalyst; recyclable; thiol